Long-Term Follow-Up of Immunocytochemical Analysis of Vascular Endothelial Growth Factor (VEGF), and Its Two Receptors, VEGF-R1 (Flt-1) and VEGF-R2 (Flk-1/KDR), in Oesophagogastric Cancer. Issue 1 (January 2013) - Gray, Ronan T.; O'Donnell, Mark E.; Maxwell, Perry; McGuigan, James A.; Spence, Gary M.
Background: The prognostic significance of immunocytochemical analysis of tumour vascular endothelial growth factor (VEGF) and its 2 receptors, VEGF-R1 and VEGF-R2, remains incompletely investigated in patients with oesophagogastric cancer. Methods: Patients undergoing surgical resection were prospectively recruited between February 1999 and August 2000. Immunocytochemical analysis of VEGF, VEGF-R1 (Flt-1) and VEGF-R2 (Flk-1/KDR) was undertaken using validated techniques. Patients were followed up over a 10-year period using the Northern Ireland Cancer Registry. Results: Sixty-one patients were recruited (male=45, 73.8%) with a median age of 66.0 years (range 39-83). Forty-seven (77.0%) adenocarcinomas and 14 (23.0%) squamous cell carcinomas were resected. UICC tumour staging was: stage I=14.7%, II=24.6%, III=54.1% and IV=6.6%. VEGF, VEGF-R1 and VEGF-R2 were over-expressed in tumour epithelial cells. VEGF-R2 expression was decreased in the presence of lymphovascular invasion and higher tumour grade. The 10-year survival rate was 19.7% (n=12) with a median follow-up of 808 (IQR 356-2313) days. On univariate analysis only lymphovascular invasion significantly predicted poor prognosis in this cohort (p=0.05). Conclusion: VEGF, VEGF-R1 and VEGF-R2 were over-expressed in tumour epithelial cells. VEGF-R2 expression was decreased in the presence of more aggressive pathological variables. Larger studies are required to assess the prognostic significance of these biomarkers in oesophagogastric cancer.